2005
DOI: 10.1038/sj.npp.1300947
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Gene Expression in the Frontal Cortex Discriminate Alcoholic from Nonalcoholic Individuals

Abstract: Alcohol dependence is characterized by tolerance, physical dependence, and craving. The neuroadaptations underlying these effects of chronic alcohol abuse are likely due to altered gene expression. Previous gene expression studies using human post-mortem brain demonstrated that several gene families were altered by alcohol abuse. However, most of these changes in gene expression were small. It is not clear if gene expression profiles have sufficient power to discriminate control from alcoholic individuals and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
254
3
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(286 citation statements)
references
References 47 publications
21
254
3
6
Order By: Relevance
“…The 10 most up or downregulated named sequences are included in Table 1 (for a complete list of EtOH-regulated genes, see Supplementary Table 1). Several genes involved in protein secretion or degradation/ubiquitination were among the most highly differentially expressed (Table 1), indicating one pathway activated by chronic EtOH exposure and withdrawal also previously identified by us (Schafer et al, 2001) and others (Liu et al, 2005). Many genes identified with significantly different expression levels have been identified previously as regulated by EtOH, or in a variety of models of neurodegenerative diseases (eg adenylate cyclase 7 and Ncr1, also see Supplementary Table 4 in supporting information online for additional characterization of concordance).…”
Section: Alcohol-withdrawal Differential Gene Expression In Male and supporting
confidence: 60%
“…The 10 most up or downregulated named sequences are included in Table 1 (for a complete list of EtOH-regulated genes, see Supplementary Table 1). Several genes involved in protein secretion or degradation/ubiquitination were among the most highly differentially expressed (Table 1), indicating one pathway activated by chronic EtOH exposure and withdrawal also previously identified by us (Schafer et al, 2001) and others (Liu et al, 2005). Many genes identified with significantly different expression levels have been identified previously as regulated by EtOH, or in a variety of models of neurodegenerative diseases (eg adenylate cyclase 7 and Ncr1, also see Supplementary Table 4 in supporting information online for additional characterization of concordance).…”
Section: Alcohol-withdrawal Differential Gene Expression In Male and supporting
confidence: 60%
“…Genetic analyses have an important role in identifying many immune-related genes associated with alcohol abuse in both rodents and humans (Kimpel et al, 2007;Liu et al, 2006;Mulligan et al, 2006). Validating several candidate genes from these studies (including Cd14, Il1ra, and Il6) through single-gene null mutations in mice confirmed that knockout of each gene resulted in decreased alcohol consumption on a two-bottle choice test (Blednov et al, 2012).…”
Section: Alcohol Glia and Neuroimmune Signalingmentioning
confidence: 96%
“…Proteomic techniques have evolved rapidly over the past few years, and the integration and interpretation of the huge amounts of data obtained from such studies are complicated by many factors. It has been shown that the magnitude of changes in brain gene and protein expression induced by alcohol exposure is less pronounced than in other diseases (Bull et al, 2001;Liu et al, 2006;Smith, 2002). Therefore, to avoid the possibility that individual diversity could overshadow the discrete differences underlying alcohol-related disorders, expression data for a large number of proteins should be combined and interpreted with rigorous appropriate statistical tests and bioinformatics.…”
Section: Fda-approved Medications For the Treatment Audsmentioning
confidence: 99%